1999
DOI: 10.1074/jbc.274.17.11582
|View full text |Cite
|
Sign up to set email alerts
|

Glu300 of Rat Carboxypeptidase E Is Essential for Enzymatic Activity but Not Substrate Binding or Routing to the Regulated Secretory Pathway

Abstract: Several recently discovered members of the carboxypeptidase E (CPE) gene family lack critical active site residues that are conserved in other family members. For example, three CPE-like proteins contain a Tyr in place of Glu 300 (equivalent to Glu 270 of carboxypeptidase A and B). To investigate the importance of this position, Glu 300 of rat CPE was converted into Gln, Lys, or Tyr, and the proteins expressed in Sf9 cells using the baculovirus system. All three mutants were secreted from the cells, but the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 46 publications
3
24
1
Order By: Relevance
“…Therefore, impaired sorting of CPE may prevent the proper targeting of proglucagon to granules. Our finding of impaired sorting of the E300Q mutant is at variance with a previous report that showed that it bound to its substrate and was sorted to granules normally in NIT3 cells (Qian et al 1999). It is not clear how CPE is missorted in N2a cells, since its C-terminal sorting domain (Fricker et al 1990) is intact in the E300Q mutant, as evidenced by our western blot results showing strong immunoreactivity in cell extracts using a C-terminal antibody.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Therefore, impaired sorting of CPE may prevent the proper targeting of proglucagon to granules. Our finding of impaired sorting of the E300Q mutant is at variance with a previous report that showed that it bound to its substrate and was sorted to granules normally in NIT3 cells (Qian et al 1999). It is not clear how CPE is missorted in N2a cells, since its C-terminal sorting domain (Fricker et al 1990) is intact in the E300Q mutant, as evidenced by our western blot results showing strong immunoreactivity in cell extracts using a C-terminal antibody.…”
Section: Discussioncontrasting
confidence: 56%
“…N2a wt cells were also stably transfected with the enzymatically inactive form of CPE, E300Q (Qian et al 1999) using Lipofectamine 2000. Stable transfectants were selected in 800 mg/ml G418, pooled and maintained in 400 mg/ml G418.…”
Section: Introductionmentioning
confidence: 99%
“…The conversion of the putative active site Glu into Gln is not expected to substantially alter the folding of the protein; this is consistent with the observation that the mutant proteins are able to bind to the substrate affinity column despite the absence of activity. A previous study of Glu 300 in CPE (the equivalent residue) also found that the mutation to Gln eliminated activity but not substrate binding or routing to the regulated secretory pathway in a neuroendocrine cell line (48). In contrast, mutants that are severely misfolded are not properly FIG.…”
Section: Discussionmentioning
confidence: 99%
“…1). This Glu, which corresponds to Glu 270 in carboxypeptidase A and B and Glu 300 in CPE, has been previously been shown to be essential for enzyme activity but not substrate binding (48). Thus, this mutation would not be predicted to have a large impact on the structure of the protein.…”
mentioning
confidence: 99%
“…Substitution of this Glu residue with a Gln abolishes the activity of CPE, but does not affect the binding of synthetic peptide substrates (Qian et al, 1999). If cCPZ functions as an enzyme, one would expect that loss of its catalytic activity should manifest itself by an inability to induce Pax3 expression.…”
Section: ---------------------------------------------mentioning
confidence: 99%